Kecernaan Jerami Padi Yang Disuplementasi Zn Lysinate dengan Teknik In Vitro - Gatot Muslim; Armina Fariani; Arfan Abrar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
This study was conducted to determine the digestibility of rice straw that supplemented with Zn Lysinate by in vitro techniques. This research was held in laboratory of Animal Feed and Nutrition, Departement of Animal Science, Faculty of Agriculture, Sriwijaya University. Completely Randomized Design (CRD) with four treatment and four replications, were used : P0 (rice straw control), P1 (rice straw with Zn Lysinate 0,1%), P2 (rice straw with Zn Lysinate 0,2%), P3 (rice straw with Zn Lysinate 0,3%). Observed parameters were dry matter digestibility (DMD), organic matter digestibity (OMD), and N-ammonia concentration.The result showed that the highest dry matter digestibility, organic matter digestibility and N-amonia were on M0 treatment ; 33,86%, 44,94%, 1,50mM respectively. Supplementation of Zn Lysinate for rice straw had effect on Dry Matter Digestibility (DMD), but had no effect on Organic Matter Digestibity (OMD) and N-Amonia concentration.